State of knowledge of the population of the vaquita (Phocoena sinus) from the Upper Gulf of California: a bibliometric analysis - Arreguín-Sánchez, Francisco; Zetina-Rejón, Manuel J.; Vergara-Solana, Francisco Javier; Del Monte-Luna, Pablo; Rodríguez-Fuentes, Marian; Arreguín-Rodríguez, Gabriela J.; Medina-Contreras, Diana; Sánchez-Velasco, Laura (Frontiers in Conservation Science, 2025)
The state of scientific knowledge about the vaquita, Phocoena sinus, is presented, a critically endangered endemic species of the Upper Gulf of California, Mexico. Several bibliographic repositories were explored, selecting Web of Science because it considers the Science Citation Index as a selection criterion. A bibliometric and bibliographic analysis of the literature was carried out. A network of associations was built based on the co-occurrence of sets of keywords, which reflect the relevance of the research topics discussed. Two sets stand out: population and conservation. Unaddressed topics are also identified, such as trophic interdependencies, ecosystem, effects of the environment and climate patterns. Regarding the population, topics such as changes in abundance, vulnerability, distribution and current habitat have been addressed. In terms of conservation, the monotonic decrease in the size of the population stands out, the management aimed at stopping this decrease and the interaction with commercial and illegal fishing. In conclusion, the measures adopted have not been effective, given that the vaquita population continues to decline. There are failures in the application of regulations, insufficient monitoring and surveillance, unregistered captures, illegal fishing and the limited participation of human communities in the design and implementation of the regulations, perceiving damages and lack of interest in compliance with the regulations and proposed measures. Beyond the knowledge gained, research is needed to answer a key question: are current habitat and ecosystem conditions suitable for the vaquita population to recover? The answer to this question requires different and even currently non-existent knowledge.